Proportion and Causes of Adolescent Fertility in South Sulawesi Province: A Population-Based Research - sadarang, rimawati aulia insani; Haerana, Bs Titi; bujawati, emmi (Riset Informasi Kesehatan, 2024)
Background: Adolescent fertility has a negative impact on their generation and the generations they are born with. This incident was motivated by multi factors, but in South Sulawesi Province it has not been studied extensively. This research aims to study the factors that influence adolescent fertility in South Sulawesi Province. Method: Population-based research that used secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS) with a cross sectional study approach. The 2017 IDHS sample is the result of a multi-stage stratified design. In this study, we filtered adolescents aged 15-19 years who lived in South Sulawesi Province resulting in 336 people. Used multivariate logistic regression with the aim of controlling for potential cofounder variables Results: 8.4% proportion of adolescent fertility. Aged 18-19 years the largest determinant of adolescent fertility (aOR=8.6; 95%CI 2.82 - 26.49), respondents never used the internet with aOR: 3.8 (95% CI 0.00 – 0.01), low education level with aOR: 6.8 (95% CI 0.79 – 59.39), being no longer in school at the time of the survey with aOR: 3.5 (95%CI 0.42 – 30.07) of experiencing teenage fertility. Fertility variables based on education level and schooling status did not show statistically significant differences, but were retained in multivariate analysis for substantial consideration. Conclusion: Aged 18-19 years, low education level, not currently in school at the time of the survey, and respondents never used the internet were determinants of adolescent fertility in South Sulawesi Province.